Comic Media Assisted SQ3R Method Influence Students Comprehensive Reading Skills - Dewi, Ni Putu Yasmita; Ganing, Ni Nyoman (Journal of Education Technology, 2020)
This research is motivated by students' reading skills that are not optimal and learning activities are less active and interesting. This study was aimed at recognizing the influence of SQ3R comic assisted method application to the comprehensive reading skills in the learning process of Indonesian of the fifth grade. Quasi-experiment with a non-equivalent control group design was conducted in this study. The populations of this study involved 248 students and the obtained sample involved 35 students of the fifth grade from the experimental group and 32 students of the fifth grade from the control group. The data analysis was conducted by using t-test and the formula of polled variance. The analyzed data was obtained tcount= 2.700 > ttable=1.997 at the significance level of 5% (df=35+32-2=65); Ha was accepted and H0 was rejected which means there was a significant difference in reading comprehension skills between groups of students who were taught with the SQ3R method assisted by comic media and groups of students who were taught with conventional learning.  Based on the explanation above, it can be concluded that the SQ3R method assisted comic effects the comprehensive reading skills in the learning process of Indonesian in the fifth grade. This research proves that the application of SQ3R method assisted by comic media in reading comprehension skills has a significant effect on Indonesian learning activities so that it affects students' reading comprehension skills in Indonesian.